Functionalization of styrene–butadiene rubber with meta‐pentadecenyl phenol for better processing: A multifunctional additive and renewable resource. Issue 31 (19th April 2017) - Mahata, Denial; Prabhavale, Onkar; Samantarai, Satyajit; Maity, Himadri; Nag, Ahindra; Nando, Golok B.
ABSTRACT: Meta‐pentadecenyl phenol, a nonisoprenoid phenolic lipid, is a renewable agricultural resource and also a byproduct of the cashew industry; it is popularly known as cardanol . This study throws light on the grafting of cardanol, which has been established as a multifunctional additive for natural rubber, onto the main‐chain backbone of styrene–butadiene rubber (SBR), a synthetic polymer used to imbibe the multifunctional properties of the former, such as those of a plasticizer, curing promoter, process aid, and antioxidant, into the latter. The grafting was carried out in the solution stage on a trial basis with a peroxide catalyst, and all of the grafting parameters were optimized with a Taguchi methodology. The grafting of cardanol onto the SBR backbone was successfully confirmed by UV–visible spectroscopy, Fourier transform infrared spectroscopy, and NMR analysis. Thermal analysis of the cardanol‐grafted styrene–butadiene rubber (C‐ g ‐SBR) revealed a higher thermal stability and better plasticizing effect than that those found in the virgin SBR. The rheological properties of the grafted rubber indicated the improvement of the pseudo‐plastic (shear‐thinning) nature compared to that in gum SBR. The unfilled C‐ g ‐SBR vulcanizates exhibited physicomechanical properties comparable to 5‐phr processing‐oil‐containing SBR [oil‐plasticized styrene–butadiene rubber (OPSBR)] vulcanizates. The carbon‐black‐filled C‐ g ‐SBR vulcanizates exhibited improved plasticization, a faster curing rate, easy processability, and better physicomechanical properties compared to the 5‐phr OPSBR vulcanizates. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45150. Abstract :